PEMBANGUNAN AGROWISATA BERBASIS PEMBERDAYAAN MASYARAKAT DI KABUPATEN BULELENG - Dewa Ayu Eka Agustini; Ni Ketut Sari Adnyani (Jurnal Pengabdian Kepada Masyarakat Media Ganesha, 2021)
This study aims to examine the mapping of regional assets and community empowerment in tourism development in Buleleng Regency and analyze the urgent strategies to be developed in generating tourism affected by the pandemic in Buleleng Regency. This research is a descriptive field research. The research sample consisted of ± 30 people, representing 10 people each. The samples were determined purposively. The data analysis technique used a qualitative descriptive analysis technique. The results showed that mapping of regional assets and community empowerment greatly determines the rate of tourism growth in Buleleng Regency. The pentahelix synergy strategy is urgent to develop in generating tourism affected by the pandemic in Buleleng Regency. Tourism recovery in Buleleng Regency is oriented towards empowerment by looking at the potential of the area coupled with the support of related stakeholders.